INTEGRASI MANAJEMEN STRATEGI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN: SINTESIS KONSEPTUAL FORMULASI–IMPLEMENTASI–EVALUASI PADA LEMBAGA PENDIDIKAN - Heri Suwarsono; Ima Widiyanah; Erny Roesminingsih; Amrozi Khamidi; Karwanto Karwanto; Syunu Triahantoyo (STKIP Pesisir Selatan, 2026)
The development of education in the era of globalization requires educational institutions to adapt through effective strategic management, particularly in improving learning quality. However, strategic management and learning are often treated as separate domains, resulting in a gap between strategic planning and classroom practices. This study aims to explain the integration of strategic management in improving learning quality through a conceptual synthesis focusing on strategy formulation, implementation, and evaluation in educational institutions. This research employs a qualitative approach using library research. Data were collected from books and relevant national and international journal articles published between 2021 and 2026 through Google Scholar. Data analysis was conducted using content analysis to identify themes, patterns, and relationships among concepts. The findings indicate that integrating strategic management into learning is a crucial aspect that has not been widely explored. Strategy formulation serves as the basis for instructional design, implementation is reflected in innovative learning practices, and evaluation functions as a reflective mechanism for continuous improvement. Therefore, this integration is essential to systematically and sustainably improve learning quality.